The Impact of New Health Transformational on Nursing Practice: A Systematic Review of Current Trends of Nursing Care and Future Directions - Nada Saleh Abushrian, Sarah Ahmed Mahah Rajhi, Halima Mohammed Humedy, Fatimah Nabit Alshahrani, Meshaal Hamud Alotibi,; Ohoud Ayesh Alharbi, Ohood Mdayish Gofashi, Munira Khaled Aldosari, Heiam Mohammed Alsahly, Maram Sultan Alosaimi, Salha Ahmed Mohammed Osis, Mariam Ali Mohammed Mahnashi, Eidah Yahya Nasser Al jarab, (Journal of International Crisis and Risk Communication Research, 2024)
Background: The rapid advancements in technologies such as the medical internet of things (MIoT), generative artificial intelligence (AI), and Healthcare 4.0 are transforming various sectors, particularly healthcare and education. While these innovations promise significant benefits, they also raise concerns regarding security, data privacy, academic integrity, and integration into existing systems. Aim: This study aims to explore the impact of emerging technologies MIoT, generative AI, and Healthcare 4.0—on healthcare and education, examining both the opportunities they offer and the challenges they present. It also investigates the ethical, security, and operational challenges posed by these technologies and provides recommendations for their effective implementation. Method: A systematic review of 10 selected studies was conducted to analyze trends, themes, and outcomes related to the adoption and integration of MIoT, generative AI in education, and Healthcare 4.0 technologies. The studies were selected based on their relevance to technological advancements, ethical considerations, and their impact on healthcare and education systems. Results: The review highlighted several key trends, including the growing concern for cybersecurity in MIoT systems, the increasing adoption of AI tools in education, and the integration challenges of Healthcare 4.0 technologies in hospitals. While these innovations promise to enhance the quality of education and healthcare services, issues such as data breaches, academic integrity, and the lack of security standards in healthcare systems remain significant barriers to their widespread adoption. Conclusion: The integration of MIoT, generative AI, and Healthcare 4.0 technologies presents both significant opportunities and challenges. To maximize their benefits, it is crucial to develop robust security frameworks, ethical guidelines, and strategies for effective integration into existing systems. Future research should focus on addressing these challenges while ensuring the responsible use of these technologies.